2005
DOI: 10.1016/j.eplepsyres.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Language activation distributions revealed by fMRI in post-operative epilepsy patients: Differences between left- and right-sided resections

Abstract: Objective: To reveal differences of cerebral activation related to language functions in post-operative temporal lobe epilepsy (TLE) patients. Methods: Right (RTL) and left temporal lobe (LTL) resected patients, and healthy controls were studied using functional magnetic resonance imaging (fMRI). Only patients with complete left-hemispheric language dominance according to the intracarotid amytal procedure (IAP) were included. Language-related activations were evoked by performing word generation and text readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Some authors have suggested that the lateralization of the EZ is the determining factor in language reorganization in patients with TLE. Patients with left EZ are more likely to show atypical language representation than healthy subjects or patients with right EZ (Adcock et al, 2003;Backes et al, 2005;Berl et al, 2005;Schwarz and Pauli, 2009;Karunanayaka et al, 2011). Similarly, Brázdil et al (2003) found that atypical organization was more common in patients with left TLE (23.1%) than patients with right TLE (0%).…”
Section: Interindividual Factorsmentioning
confidence: 87%
See 1 more Smart Citation
“…Some authors have suggested that the lateralization of the EZ is the determining factor in language reorganization in patients with TLE. Patients with left EZ are more likely to show atypical language representation than healthy subjects or patients with right EZ (Adcock et al, 2003;Backes et al, 2005;Berl et al, 2005;Schwarz and Pauli, 2009;Karunanayaka et al, 2011). Similarly, Brázdil et al (2003) found that atypical organization was more common in patients with left TLE (23.1%) than patients with right TLE (0%).…”
Section: Interindividual Factorsmentioning
confidence: 87%
“…These factors may include demographic and clinical characteristics of patients, such as the age at which the lesion or epileptic seizures occur (Vargha-Khadem et al, 1997;Staudt et al, 2001;Hertz-Pannier et al, 2002;Liégeois et al, 2004;Brázdil et al, 2005;Tracy et al, 2009), the size, location, and lateralization of the EZ (Adcock et al, 2003;Backes et al, 2005;Berl et al, 2005;Karunanayaka et al, 2011), frequency of interictal epileptiform discharges (Janszky et al, 2003(Janszky et al, , 2006, gender (Strauss et al, 1992;Helmstaedter et al, 2004), handedness (Berl et al, 2014), and individual differences in potential plasticity (Zatorre, 2013). Furthermore, the pattern of organization may be different before and after surgery (Helmstaedter et al, 2006;Bonelli et al, 2012;Perrone-Bertolotti et al, 2012a).…”
Section: Factors Modulating Language Plasticity In Epilepsy Patientsmentioning
confidence: 99%
“…They identified expressive language sites substantially anterior and superior to canonical Broca's area, which they attributed to intrahemispheric reorganisation associated with left hemisphere insult from a young age resulting in an anterior displacement of language within the frontal lobe. Neuroimaging studies reporting reorganisation of language function also suggest a degree of inherent cortical plasticity (Hertz-Pannier et al, 2002;Backes et al, 2005;Pataraia et al, 2005;Yuan et al, 2006). Evidence of reorganisation of left hemisphere language function to mirrored sites in the right hemisphere following left hemispherectomy suggests that there may be a pre-existing bilateral language network (Hertz-Pannier et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…About 70% of patients who undergo resection surgery for seizures originating from regions within the anterior/mesial temporal lobes have a positive outcome and the majority are completely seizure free after the procedure (Backes et al 2005). Despite careful pre-surgical screening, about 30% of patients undergoing a temporal lobectomy experience temporary or permanent deficits related to language and/or memory functions (Baxendale et al 2008).…”
Section: Introductionmentioning
confidence: 98%